Rekonstruksi Fantom Toraks Menggunakan Nilai Densitas Hounsfield Unit sebagai Fantom Alternatif untuk Verifikasi Dosis Radiasi - Fiqi Diyona; Afdhal Muttaqin; Rhandyka Rafli (Universitas Andalas, 2025)
Phantoms play an essential role in medical physics, particularly for radiation dose verification, yet the high cost of commercial standard phantoms often limits their availability. This study aimed to reconstruct a thoracic phantom as a replica of the human chest cavity using simple and low-cost materials. The reconstruction process began with evaluating the density values of the selected materials: cadaver bone was used as a substitute for human bone, styrofoam for lung tissue, and plasticine for soft tissues such as muscle and fat. Density measurements showed that cadaver bone ranged from +350 HU to +1000 HU, styrofoam from –700 HU to –950 HU, and plasticine from +39 HU to +234 HU. The skeletal-based reconstruction successfully represented the anatomical alignment of thoracic organs, as confirmed by CT simulator imaging. These findings indicate that the reconstructed thoracic phantom provides a feasible and cost-effective alternative to expensive commercial phantoms and can be effectively utilized for radiation dose verification in medical physics applications.